Durvalumab after sequential chemoradiotherapy in unresectable stage III non-small-cell lung cancer - final analysis from the phase II PACIFIC-6 trial - Garassino, Marina; Khalifa, J.; Reck, M.; Chouaid, C.; Bischoff, Helge; Reinmuth, N.; Cove-Smith, L.; Mansy, T.; Cortinovis, D. L.; Migliorino, M. R.; Delmonte, A.; Garcia Sánchez, J.; et al. (ESMO open, 2025)
Background - Durvalumab after concurrent chemoradiotherapy (cCRT) is the standard of care for patients with unresectable, stage III non-small-cell lung cancer (NSCLC). However, patients often receive sequential chemoradiotherapy (sCRT) due to factors including advanced age or frailty, comorbidities, or disease- or access-related concerns. The phase II PACIFIC-6 trial (NCT03693300) evaluated the safety of durvalumab after sCRT in this setting. Interim results indicated a similar safety profile to that observed with durvalumab after cCRT, with encouraging preliminary efficacy. We report outcomes from the final analysis. - Patients and methods - Adults with unresectable, stage III NSCLC, Eastern Cooperative Oncology Group performance status ≤2, and no disease progression following platinum-based sCRT were enrolled to receive durvalumab 1500 mg intravenously once every 4 weeks for up to 24 months. The primary endpoint was the incidence of grade 3/4 adverse events (AEs) possibly related to treatment (PRAEs) occurring within 6 months. Secondary endpoints included overall survival (OS) and progression-free survival (PFS; investigator assessed as per RECIST v1.1). - Results - As of 20 March 2023, 117 patients (65.8% aged ≥65 years; 98.3% with past or present comorbidities) were enrolled. Overall, 27.4% of patients had grade 3/4 AEs and 6.0% had grade 3/4 PRAEs, including two patients (1.7%) with pneumonitis. Three patients (2.6%) had fatal AEs, with one (0.9%) having a fatal PRAE (pneumonitis). Overall, 27.4% discontinued durvalumab due to AEs. Median follow-up was 32.6 and 30.2 months among patients censored for OS and PFS, respectively. Median OS was 39.0 months [95% confidence interval (CI) 30.6 months-not calculable]; 3-year OS rate was 56.5% (95% CI 46.4% to 65.5%). Median PFS was 13.1 months (95% CI 7.4-19.9 months); 2-year PFS rate was 35.3% (95% CI 26.5% to 44.3%). - Conclusions - Durvalumab after sCRT was well tolerated and could be an alternative treatment strategy when cCRT is not feasible. Confirmatory randomized phase III data are awaited.